History of kidney stones and risk of chronic kidney disease: a meta-analysis - Shang,Weifeng; Li,Lixi; Ren,Yali; Ge,Qiangqiang; Ku,Ming; Ge,Shuwang; Xu,Gang (PeerJ, 2017)
Background Although the relationship between a history of kidney stones and chronic kidney disease (CKD) has been explored in many studies, it is still far from being well understood. Thus, we conducted a meta-analysis of studies comparing rates of CKD in patients with a history of kidney stones. Methods PubMed, EMBASE, and the reference lists of relevant articles were searched to identify observational studies related to the topic. A random-effects model was used to combine the study-specific risk estimates. We explored the potential heterogeneity by subgroup analyses and meta-regression analyses. Results Seven studies were included in this meta-analysis. Pooled results suggested that a history of kidney stones was associated with an increased adjusted risk estimate for CKD [risk ratio (RR), 1.47 95% confidence interval (CI) [1.23–1.76])], with significant heterogeneity among these studies (I2 = 93.6%, P < 0.001). The observed positive association was observed in most of the subgroup analyses, whereas the association was not significant among studies from Asian countries, the mean age ≥50 years and male patients. Conclusion A history of kidney stones is associated with increased risk of CKD. Future investigations are encouraged to reveal the underlying mechanisms in the connection between kidney stones and CKD, which may point the way to more effective preventive and therapeutic measures.
Keywords: Meta-analysis; Nephrolithiasis; Chronic kidney disease; Kidney stones